2016
DOI: 10.1007/jhep10(2016)137
|View full text |Cite
|
Sign up to set email alerts
|

2D Kac-Moody symmetry of 4D Yang-Mills theory

Abstract: Scattering amplitudes of any four-dimensional theory with nonabelian gauge group G may be recast as two-dimensional correlation functions on the asymptotic twosphere at null infinity. The soft gluon theorem is shown, for massless theories at the semiclassical level, to be the Ward identity of a holomorphic two-dimensional G-Kac-Moody symmetry acting on these correlation functions. Holomorphic Kac-Moody current insertions are positive helicity soft gluon insertions. The Kac-Moody transformations are a CP T inva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
285
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(300 citation statements)
references
References 63 publications
7
285
0
Order By: Relevance
“…The authors of [5] moreover related the subleading soft graviton functions to a conjectured hidden symmetry of the quantum gravity S-matrix [6,7] which has the form of an extended BMS 4 algebra [8][9][10] known from classical gravitational waves. Similar claims that the Yang-Mills S-matrix enjoys a hidden two-dimensional Kac-Moody type symmetry were made recently [11]. In this picture the scattering amplitudes in four-dimensional quantum field theory are related to correlation functions of a two-dimensional quantum theory living on the sphere at null infinity.…”
Section: Introduction and Conclusionsupporting
confidence: 64%
“…The authors of [5] moreover related the subleading soft graviton functions to a conjectured hidden symmetry of the quantum gravity S-matrix [6,7] which has the form of an extended BMS 4 algebra [8][9][10] known from classical gravitational waves. Similar claims that the Yang-Mills S-matrix enjoys a hidden two-dimensional Kac-Moody type symmetry were made recently [11]. In this picture the scattering amplitudes in four-dimensional quantum field theory are related to correlation functions of a two-dimensional quantum theory living on the sphere at null infinity.…”
Section: Introduction and Conclusionsupporting
confidence: 64%
“…9 Emergent CS and "shadow" effects from boundary/soft limits In Mink 4 gauge theory, it was shown that AS and memory effects arise from considering same-helicity gauge boson emissions in the soft limit [6,7]. Ref.…”
Section: Jhep01(2018)014mentioning
confidence: 99%
“…Considerable progress has been made in this regard by the discovery that the associated large diffeomorphisms and gauge transformations arise as soft limits of physical gravitational and gauge fields emerging from scattering processes [5][6][7][8][9][10][11][12][13][14][15], as captured by the Weinberg Soft Theorems [16][17][18][19][20]. The infinite-dimensional AS then describe the soft field dressing of a hard process, and are sensitive to the passage of charge/energy-momentum as a function of angle, through "memory" effects [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding Ward identities are equivalent to gauge theory soft theorems [19,20]. Moreover, it was shown, that scattering amplitudes of any four-dimensional theory with nonabelian gauge group G may be recast as two-dimensional correlation functions on the asymptotic twosphere at null infinity [20].…”
Section: Jhep12(2015)030mentioning
confidence: 99%